Representativeness of the Swiss Diabetes Registry – a single centre analysis (Swiss Medical Weekly, 2021)
OBJECTIVE The Swiss Diabetes Registry (SwissDiab) is a multicentre, longitudinal, observational study of outpatients with diabetes receiving treatment at tertiary care centres. The aim of this study was to evaluate the representativeness of the participants at the study centre in the Division of Endocrinology and Diabetes at the Cantonal Hospital of St Gallen by comparing diabetes-related characteristics of participating and nonparticipating patients. METHODS The study included 493 SwissDiab participants enrolled between 1 January 2010 and 31 December 2016 and 640 nonparticipating patients treated at the centre during the same time period. For participants and nonparticipating patients, demographic characteristics, clinical findings, blood chemistry and medication were retrieved from the SwissDiab baseline visit and the medical record ±6 months from the first available outpatient visit to the clinic for diabetes-related care within the study period. Nonparticipating patients were further divided into three subgroups: (i) excluded from SwissDiab, or having received (ii) ≥6 months or (iii)